Developing of Tris Soy Milk Diluent for Frisian Holstein Bull Frozen Semen - ARIFIANTINI, RADEN IIS; YUSUF, TUTY LASWARDI (HAYATI Journal of Biosciences, 2010)
Commercial artificial insemination (AI) companies in the beginning of year 2000, introduced new generation of cryoprotectans with lecithin based diluents such as Biociphos (IMV, L’Aigle, France) and Andromed®  (Minitub, Germany). Since the commercial diluents were imported, they were often not readily available. This research aimed to develop Tris-soy modified diluent, and investigated its effects on the quality and fertility of Frisian Holstein (FH) bulls frozen semen. This research consists of two experiments. At first, we compared the FH Bull frozen semen quality in modified tris soy milk (TSM), Andromed® and Tris-eggyolk (TEY) diluents, the second  was the fertility trials of the frozen semen. Results of the experiment demostrated that post thawed sperm motility in the semen preserved with TEY (49.10%) or Andromed® (50.21%) was significantly higher (P = 0.037) than that preserved with TSM (41.53%). In contrast, the conception rates in cows inseminated with semen preserved with TSM, TEY, and Andromed® were 53.84% (7/13), 38.88% (5/13), and 38.46% (7/19), respectively. We are optimistic that TSM diluents will have similar qualities as TEY and Andromed® on preserving frozen semen by doing future intensive studies.